Effect of Donepezil on Cognitive Deficits Associated With Electroconvulsive Therapy: A Randomized Triple-blind Clinical Trial. Issue 2 (March 2019) - Shams-Alizadeh, Narges; Maroufi, Azad; Sofla, Akbar Qanbarzadeh Chelan; Ghaderi, Ebrahim; Hassanzadeh, Kambiz
Abstract : Objectives: Despite the effectiveness of electroconvulsive therapy (ECT) in a wide range of psychiatric disorders, the role of memory-enhancing agents in post-ECT cognitive disturbances has remained controversial. In this study, we aimed to assess the effect of donepezil on improving the cognitive performance of patients undergoing ECT. Methods: In a psychiatry hospital, patients who were admitted for ECT underwent a triple-blind randomized controlled trial. After randomizing the participants into 2 groups, 1 group received ECT with placebo, whereas the other group received ECT plus 5 mg/d donepezil during the ECT period. The patients in both groups were cognitively assessed using the Mini Mental Status Evaluation and Wechsler Memory Scale, 24 hours before ECT and 48 hours after the end of the ECT sessions. Results: The results of Mini Mental Status Evaluation scores did not show any significant difference in memory performance between the 2 groups before and after ECT ( F = 0.108, P = 0.743). Moreover, the intervention and placebo groups did not have any significant difference in the scores of the 7 subscales of the Wechsler Memory Scale after ECT ( P = 0.07). In addition, the patients on donepezil group tolerated the drug well and did not differ significantly compared with the control group in this regard. Conclusions: Despite a few evidence confirming the effect of acetylcholinesterase inhibitors in improving cognitive defects related to ECT, this study did not find such an effect in patients under ECT. Further studies are required to reach a clear conclusion.